Comparative Study : Determinant On Banking Profitability Between Buku 4 And Buku 3 Bank In Indonesia - Andy Setiawan; Bambang Hermanto (Benefit: Jurnal Manajemen dan Bisnis, 2017)
This research is performed on order to analyze the influence of Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), and Operating Expense to Operating Income Ratio (OEOI) as independent variable toward Return on Asset (ROA) and Return on Equity (ROE) as dependent variable. Sample for this research is all of BUKU 4 banks and seven banks on BUKU 3 banks  in Indonesia in 2006-2015 period. Data analysis with multi liniear regression. The result of  this research shows that all of independent variables have significant influence on ROA and ROE simultaneously.  NIM has partially significant effect on profitability both in BUKU 3 and BUKU 4 banks but other variables have various effect on profitability. The amount of the contribution or influence independent variables to ROA are 64,7%  in BUKU 3 banks and 90,4% on BUKU 4 banks. Meanwhile contribution of independent variables to ROE are 55,4% in BUKU 3 banks and 74,1% in BUKU 4 banks.